Ion-irradiation-induced clustering in W–Re and W–Re–Os alloys: A comparative study using atom probe tomography and nanoindentation measurements. (1st April 2015) - Xu, Alan; Beck, Christian; Armstrong, David E.J.; Rajan, Krishna; Smith, George D.W.; Bagot, Paul A.J.; Roberts, Steve G.
Abstract: This study examines clustering and hardening in W–2 at.% Re and W–1 at.% Re–1 at.% Os alloys induced by 2 MeV W + ion irradiation at 573 and 773 K. Such clusters are known precursors to the formation of embrittling precipitates, a potentially life-limiting phenomenon in the operation of fusion reactor components. Increases in hardness were studied using nanoindentation. The presence of osmium significantly increased post-irradiation hardening. Atom probe tomography analysis revealed clustering in both alloys, with the size and number densities strongly dependent on alloy composition and irradiation temperature. The highest cluster number density was found in the ternary alloy irradiated at 773 K. In the ternary alloy, Os was found to cluster preferentially compared to Re. The implications of this result for the structural integrity of fusion reactor components are discussed.